Detection of hydrological alteration and soil erosion in a conserved tropical sub-humid ecosystem of Ethiopia - Tebeje, A. K.; Hussein, M. A.; Assefa, T. T.; Mhiret, D. A.; Zimale, F. A.; Abebe, W. B.; Adem, A. A.; Tilahun, Seifu A.; Desta, G.; Ahmed, M. A. (Elsevier, 2024)
Soil erosion poses a significant challenge in the sub-humid Ethiopian highlands, yet research on the long-term effectiveness of soil and water conservation (SWC) practices in this region using pre- and post-conservation approaches remains limited. This study addresses this knowledge gap by evaluating the impact of SWC practices on water balance and soil erosion in the Debre Mawi watershed. The study covers two-period analyses: pre-conservation (2010–2014) and post-conservation (2015–2022) using the Soil and Water Assessment Tool (SWAT) to simulate hydrological water balance. Hydrological changes were assessed with the Indicators of Hydrological Alteration (IHA) software. Spatial and weekly sediment distribution were also computed. Results showed the SWAT effectively simulated stream flow, though sediment yield estimation was less accurate. The data demonstrated a reduction in surface runoff by 18% and a decrease in sediment yield by 75%. Conversely, evapotranspiration and groundwater storage experienced increases of 13% and 34%, respectively. The decrease in runoff and sediment can be attributed to the implementation of SWC structures with infiltration furrows, which are presently filled with sediment. Moreover, the expansion of eucalyptus tree acreage may deplete soil water during dry periods, thereby prolonging the time needed for the soil to become saturated and produce runoff, but the impact has yet to be quantified. The IHA analysis confirmed a decrease in mean annual flow from 0.06 m3 /s to 0.02 m3 /s, and sediment concentration decreased from 831.2 mg/l to 285 mg/l between the pre-and post-conservation periods. The study detected that soil erosion is higher than the allowable limits recommended for Ethiopia even after implementing SWCPs. Additionally, sediment transport reduced after the first three weeks due to improved ground cover and soil stability, although significant amounts were recorded until the end of the rainy season, primarily from gullies. The study found significant hydrological alterations in flow and sediment dynamics following the implementation of SWC practices, particularly pronounced in the early years post-conservation (2015–2018). However, the effectiveness of SWC practices diminished over time, with conditions beginning to revert to pre-conservation levels after 10 years. This suggests that these techniques (infiltration furrows) may be unsuitable for sub-humid watersheds, or that they require improved design and major maintenance beyond the third year. This study offers valuable insights into the dynamics of SWC interventions, underscoring the importance of integrating agronomic practices with SWC efforts to sustain long-term soil and water conservation in Ethiopia’s sub-humid highlands. Future research should explore the hydrological effects of eucalyptus expansion and refine SWC practices suited to these unique conditions.